Symbolic Interaction of Character Personality in the 5 Panca Wanda Mask - Imawan, Khaerudin; Ragil, Muhammad; Kusuma, Wahyu Dwa (International Journal of Social Service and Research, 2025)
This study aims to explore how symbolic interaction shapes the personalities of characters in the 5 Panca Wanda Mask performance. The purpose of this study is to determine the characters and dance styles in 5 Panca Wanda Mask, and to educate the people of Cirebon to know that the Mask Dance was created in order to spread Islam. By relying on George Herbert Mead's symbolic interaction theory and Sugiyono's qualitative approach, we try to understand how the symbols in the masks reflect the stages of human personality development. In 5 Panca Wanda Mask, there are five characters Panji, Samba, Rumyang, Tumenggung, and Kelana, each of which symbolizes a different phase of life, from babies, children, teenagers, to adults. Their characters are depicted through facial expressions, colors, movements, and the way they interact on stage. As a result, this performance reflects the process of individual identity formation as explained by Mead, namely the stages of imitation, play, and group play. Symbols in masks are not only a means of communication, but also shape people's understanding of a person's role and existence. So, this study opens up insight into how traditional performing arts can be a reflection of the process of social interaction that shapes human personality.